Business Model Canvas: Odor Absorbent Dustbin / Nur Fakhriah Aziela Abu Sepian - Abu Sepian, Nur Fakhriah Aziela (2020)
This report has been dedicated to discuss the business canvas model of Odor Absorbent Dustbin. In this regard, the customer has been segmented especially for household. This product are newness from the other dustbin and also long lasting dustbin and performance. This product can be commercial in the store and also online store. The money can be gain from the primary revenue and also from the youtube channel of our new product. The key partners of the business have been discussed and the key services include the manufacturing, assembly and distribution of company’s product. The company is creating value through provision of latest technology products and by handling customer’s needs and complaints. . It is operating with many sources amongst them; the key resources are the people who are employees of the company, its physical assets and intellectual properties. The cost structure are organized in R&D, raw material and marketing department